2021
DOI: 10.3171/2020.9.jns201976
|View full text |Cite
|
Sign up to set email alerts
|

Double-barrel STA-MCA bypass for cerebral revascularization: lessons learned from a 10-year experience

Abstract: OBJECTIVE In select patients, extracranial-intracranial (EC-IC) bypass remains an important tool for cerebral revascularization. Traditionally, superficial temporal artery–middle cerebral artery (STA-MCA) bypass was performed using one limb of the STA only. In an attempt to augment flow and to direct flow to different ischemic areas of the brain, the authors adopted a “double-barrel” technique in which both branches of the STA are used to revascularize distinct MCA territories. METHODS A series of consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In this study’s keyword analysis, we identified several significant research hot spots in the field of cerebral revascularization over the past two decades, including “cerebral revascularization,” “moyamoya disease,” “surgery,” “extracranial intracranial bypass,” “occlusion,” “revascularization,” “superficial temporal artery,” “aneurysm,” “stroke,” and “internal carotid artery” ( Table 6 ). We subsequently reviewed the relevant literature and discovered that, in recent years ( Gunawardena et al, 2019 ; Kan et al, 2021 ), “extracranial intracranial bypass” or “STA-MCA bypass” is the most important neurosurgical treatment in the field of cerebral revascularization, and the majority of them have significant effects on the treatment and prognosis of moyamoya disease, for instance, the safety of STA-MCA bypass in the treatment of moyamoya disease ( Liu et al, 2017 ), the hemodynamic problems of STA-MCA bypass in the treatment of moyamoya disease ( Jeffree and Stoodley, 2009 ), the significance of Color Doppler monitoring of STA-MCA bypass in the treatment of moyamoya disease ( Kawamata et al, 2011 ; Feghali et al, 2019 ). However, we employed keyword clustering analysis to determine the tight association within the cerebral revascularization research field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study’s keyword analysis, we identified several significant research hot spots in the field of cerebral revascularization over the past two decades, including “cerebral revascularization,” “moyamoya disease,” “surgery,” “extracranial intracranial bypass,” “occlusion,” “revascularization,” “superficial temporal artery,” “aneurysm,” “stroke,” and “internal carotid artery” ( Table 6 ). We subsequently reviewed the relevant literature and discovered that, in recent years ( Gunawardena et al, 2019 ; Kan et al, 2021 ), “extracranial intracranial bypass” or “STA-MCA bypass” is the most important neurosurgical treatment in the field of cerebral revascularization, and the majority of them have significant effects on the treatment and prognosis of moyamoya disease, for instance, the safety of STA-MCA bypass in the treatment of moyamoya disease ( Liu et al, 2017 ), the hemodynamic problems of STA-MCA bypass in the treatment of moyamoya disease ( Jeffree and Stoodley, 2009 ), the significance of Color Doppler monitoring of STA-MCA bypass in the treatment of moyamoya disease ( Kawamata et al, 2011 ; Feghali et al, 2019 ). However, we employed keyword clustering analysis to determine the tight association within the cerebral revascularization research field.…”
Section: Discussionmentioning
confidence: 99%
“…In this study's keyword analysis, we identified several significant research hot spots in the field of cerebral revascularization over the past two decades, including "cerebral revascularization, " "moyamoya disease, " "surgery, " "extracranial intracranial bypass, " "occlusion, " "revascularization, " "superficial temporal artery, " "aneurysm, " "stroke, " and "internal carotid artery" (Table 6). We subsequently reviewed the relevant literature and discovered that, in recent years (Gunawardena et al, 2019;Kan et al, 2021), "extracranial intracranial bypass"…”
Section: Hot Spots and Frontiersmentioning
confidence: 99%
“…Surgical techniques can be classified into three groups: direct, indirect, and combined revascularization procedures. Direct revascularization, which has been performed in MMA patients since the 1970s, consists of a direct extracranial-intracranial bypass, which could be an STA to MCA bypass, as performed in most cases, or a middle meningeal artery (MMA) to MCA bypass [99][100][101][102]. Anterior cerebral arteries could also be considered as receiving vessels if severe ischemia is found in the ACA area.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Recently, direct double-barrel STA to MCA bypass has been applied in the reconstruction of regional cerebral blood flow for giant intracranial aneurysms and Moyamoya disease. 12 This type of anastomosis allows distal MCA (M4) to be the recipient sites, which improves operability and makes the recipient's vessels easier to obtain. Given that its capacity for blood flow supply has not been well documented, we retrospectively investigated patients with complex intracranial aneurysms who received this procedure in our center during the past 5 years and assessed this bypass' ability to provide blood flow for distal parent artery areas.…”
mentioning
confidence: 99%